Isolated nasopharyngeal tuberculosis in a 12 year old boy – A case report - Santosh Kumar Swain; Mahesh Chandra Sahu (Egyptian Pediatric Association Gazette, 2018)
Tuberculosis is a chronic infectious disease of the human being caused by Mycobacterium tuberculosis. Tuberculosis is a major health problem in developing country in the world. Majority of the tubercular lesions confined to the lungs of the human body whereas isolated nasopharyngeal tuberculosis affect nasopharynx without involving lungs or any other organs of the body. Isolated nasopharyngeal tuberculosis is an extremely rare clinical entity in children. Most clinician do not consider tuberculosis in their differential diagnosis when patient present with nasopharyngeal symptoms, so often lead to misdiagnosis and inappropriate treatment. The incidence of pulmonary tuberculosis is declining in result of anti-tuberculosis treatment. However, the incidence of tuberculosis in developing country is increasing. Isolated nasopharyngeal tuberculosis is a rare even in the endemic areas. There are varied clinical presentations of nasopharyngeal tuberculosis. Biopsy and histopathological examination should be done in every case for avoiding misdiagnosis. Nasopharyngeal tuberculosis has an excellent prognosis and it has complete resolution if treated properly. Unexplained and prolonged upper respiratory manifestations with mass or ulcerative lesions at the nasopharynx give suspicion of nasopharyngeal tuberculosis. So clinician should keep in mind for the possibility of tuberculosis in the differential diagnosis of nasopharyngeal mass as the incidence of tuberculosis is steadily increasing in developing and developed countries. Here we are reporting a proved case of isolated Mycobacterium tuberculosis at the nasopharynx. We recommend endoscopic examination of the nasopharynx for any chronic nasopharyngeal complaints of the patients including children to rule out tuberculosis and its early treatment. Keywords: Nasopharynx, Tuberculosis, Nasopharyngeal tuberculosis